The Law Protection of The Hospital In Cooperation With Health BPJS Contract - Herni Budiyanti (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Characteristic of the contract of cooperation between bpjs health with hospitals is the contract of public, so that the contents of the contract is what i instruct you tie these two sides.As long as the complexity of the hospital care make a rather complex and difficult negotiated by the hospital when the fine print. pre-contract and it is time for the Walk contract always of the nature of a monopoly parties bpjs health are more dominant.And household characteristics sick with another.And yet the reason uniformity contract the hospital across Indonesia the contents of an agreement at the same.It is pretty obvious that a lot of difference basic in the perspective of the project, human resources and different working capital. The principle of proportional meaningful his exchange that provide the basis or form the basis of the rights and obligations of the parties in accordance proportion or its part of the whole process of contractual arrangement.The principle of proportionality presupposes the division of the rights and obligations of manifested in the whole process of contractual arrangement, good at phase pre-contractual, the formation of a contract and the implementation of the contract ( pre-contractual, contractual, post contractual.The principle of proportional transcendental the context of its relations and the interests of the parties ( maintain the sustainability of the relations that take place conducive and fair ). Legal protection for hospitals there are for example through a contract that has been signed with a signature that is be law enforcement for both sides.